DESAIN PENELITIAN EKSPERIMEN DALAM MANAJEMEN PENDIDIKAN ISLAM - Zaskia; Dina Hermina; Salmah (PT. Hasba Edukasi Mandiri, 2026)
This study aims to conceptually examine experimental research designs in Islamic education management. The research employs a qualitative approach using a library research method, drawing data from scientific journals, methodological books, and relevant academic publications. Data were analyzed using content analysis to identify concepts, characteristics, and the application of experimental designs within the context of Islamic education. The findings indicate that experimental designs play a significant role in supporting evidence-based decision-making through the examination of causal relationships. Three main types of experimental designs are identified: true experimental, quasi-experimental, and pre-experimental, each with different levels of validity and limitations. In the context of Islamic education management, the implementation of experimental designs faces structural, cultural, and ethical challenges, particularly in institutions such as madrasahs under the Kementerian Agama Republik Indonesia, pesantren, and Islamic schools. Therefore, selecting adaptive and contextual designs is necessary to maintain methodological relevance. This study contributes theoretically to strengthening research methodology in Islamic education.